Ethical dilemmas in orthodontics. (2nd April 2019) - Burns, Angus J; Noar, Joseph H
Abstract : Those practising orthodontics frequently face ethical dilemmas. This article seeks to explore dilemmas, which the authors consider arise often in the field of orthodontics. The emphasis is on best practice, evidence-based practice and prioritizing patients' interests. CPD/Clinical Relevance: The intention of this article is to encourage thought and debate regarding everyday orthodontic decision-making.